2004
DOI: 10.2527/2004.8241206x
|View full text |Cite
|
Sign up to set email alerts
|

Free-range rearing of pigs during the winter: Adaptations in muscle fiber characteristics and effects on adipose tissue composition and meat quality traits1

Abstract: This research aimed to determine whether outdoor free-range rearing during the winter (average ambient temperature of 5 degrees C) vs. indoor housing (22 degrees C) affects meat quality, muscle metabolic traits, and muscle fiber characteristics. Forty Large White gilts and barrows were blocked by weight within each gender (20 per gender) and allotted randomly into two groups of pigs, with one reared indoors (IN) in individual pens (2.6 m2) and the other reared outdoors (OUT) from December to March in a 0.92-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 29 publications
8
47
3
Order By: Relevance
“…Deeper investigations would be helpful to better characterize the influence of extensive rearing conditions on p.m. muscle physiology and metabolism. In contrast with our findings, the literature generally reports no effect of extensive v. indoor rearing on the pH1 value in local (Labroue et al, 2000 in Basque and Gascon; Pugliese et al, 2005 in Cinta Senese pigs) or conventional breeds (Bee et al, 2004;Terlouw et al, 2009). Besides, the higher pre-slaughter physical activity of BE than BC pigs, which requires consumption of muscle energy (glycogen) store, would have probably contributed to their higher pHu values.…”
Section: Meat Quality Indicatorscontrasting
confidence: 99%
See 2 more Smart Citations
“…Deeper investigations would be helpful to better characterize the influence of extensive rearing conditions on p.m. muscle physiology and metabolism. In contrast with our findings, the literature generally reports no effect of extensive v. indoor rearing on the pH1 value in local (Labroue et al, 2000 in Basque and Gascon; Pugliese et al, 2005 in Cinta Senese pigs) or conventional breeds (Bee et al, 2004;Terlouw et al, 2009). Besides, the higher pre-slaughter physical activity of BE than BC pigs, which requires consumption of muscle energy (glycogen) store, would have probably contributed to their higher pHu values.…”
Section: Meat Quality Indicatorscontrasting
confidence: 99%
“…Moreover, the higher level of physical activity of extensively reared pigs that is generally associated with increased muscle oxidative metabolism (Gondret et al, 2005 for review) could also partly explain the darker colour of BE pork, in accordance with reports of Millet et al (2005). In agreement with our results, reduced meat lightness and water loss have been observed in outdoor pigs by Pugliese et al (2005), whereas Bee et al (2004) reported lower meat lightness but higher drip in outdoor v. indoor pigs. Despite higher pH1 and pHu and lower drip, which have all been positively associated with mechanical tenderness of pork (Huff-Lonergan et al, 2002;Bee et al, 2007), BE pigs had higher meat shear force values than BC pigs.…”
Section: Meat Quality Indicatorssupporting
confidence: 91%
See 1 more Smart Citation
“…The replication differences in ambient temperature were more pronounced in hoop systems compared with confinements. Fluctuations in ambient temperature due to alternative production systems have been shown to influence fatty acid composition in pigs (Lefaucheur et al, 1991;Lebret et al, 2002;Bee et al, 2004). Overall, outdoor-produced pigs have been shown to deposit more PUFA than their confinement counterparts (Bee et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial variation in growth performance and pork quality has been noted in opposing seasons, as well as between confinement and deep-bedded systems (Lebret et al, 2002;Honeyman and Harmon, 2003). Seasonal alterations in fatty acid profiles (Cava et al, 2000;Bee et al, 2004), flavour attributes of fresh pork, including intensity and pork flavour (Gentry et al, 2002b), and overall flavour acceptability (Enfalt et al, 1997) have also been noted between pigs finished in deep-bedded and outdoor systems compared with indoor systems.…”
Section: Introductionmentioning
confidence: 99%